2020
DOI: 10.7717/peerj.8831
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic model of combined ceRNA and DNA methylation related genes in esophageal carcinoma

Abstract: Esophageal cancer is a common malignant tumor in the world, and the aim of this study was to screen key genes related to the development of esophageal cancer using a variety of bioinformatics analysis tools and analyze their biological functions. The data of esophageal squamous cell carcinoma from the Gene Expression Omnibus (GEO) were selected as the research object, processed and analyzed to screen differentially expressed microRNAs (miRNAs) and differential methylation genes. The competing endogenous RNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…We focused on studying lncRNAs which were found upregulated in ESCC in the current study. LncRNAs, such as LUCAT1, KCNMB2-AS1, CASC15, MIAT, PTOV1-AS2, LINC00680, and RNF217-AS1 [ 45 50 ] were reported to be up-regulated in ESCC and other malignant tumors, validating our RNA-sequencing results. In particular, the high expression of four lncRNAs including LINC00680, AC092910.3, MIR4435-2HG, and GSEC were found to be correlated with poor prognosis in ESCC patients in lnCAR database [ 51 ], suggesting they are functionally important and clinically relevant (Fig.…”
Section: Resultssupporting
confidence: 85%
“…We focused on studying lncRNAs which were found upregulated in ESCC in the current study. LncRNAs, such as LUCAT1, KCNMB2-AS1, CASC15, MIAT, PTOV1-AS2, LINC00680, and RNF217-AS1 [ 45 50 ] were reported to be up-regulated in ESCC and other malignant tumors, validating our RNA-sequencing results. In particular, the high expression of four lncRNAs including LINC00680, AC092910.3, MIR4435-2HG, and GSEC were found to be correlated with poor prognosis in ESCC patients in lnCAR database [ 51 ], suggesting they are functionally important and clinically relevant (Fig.…”
Section: Resultssupporting
confidence: 85%
“…LncRNA gamma-butyrobetaine hydroxylase 1 (BBOX1)-antisense RNA 1 (AS1) exists as an oncogene in most tumor cells. Abnormally high expression levels of BBOX1-AS1 are observed in most cancers, such as lung [ 7 ], cervical [ 8 ], and esophageal cancers [ 9 ], and BBOX1-AS1 is strongly linked to the overall survival of patients with these cancers, which suggests that targeting BBOX1-AS1 may be used as a therapeutic approach for cancer treatment. However, the regulatory effects of BBOX1-AS1 on OSCC development have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Among these 8 lncRNAs, we further screened out 3 lncRNAs (LINC01503, NR2F1-AS1, and RNF217-AS1) for further investigations because the fold-changes of these 3 lncRNAs were the highest in TCGA SC samples versus the normal group. LINC01503 (Ding et al 2021 ), NR2F1-AS1 (Zuo et al 2021 ), and RNF217-AS1 (Guan et al 2020 ) have been found to be implicated in the pathogenesis of multiple cancers including SC. For instance, NR2F1-AS1 loss notably weakened the proliferative, migratory, and invasive abilities of SC cells (Li et al 2022a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…RNF217-AS1, an antisense transcript for RNF217, is initially deemed to be a lncRNA transcript (Fontanari Krause et al 2014 ). RNF217-AS1 has been found to be differentially expressed and to be associated with the prognosis of patients in esophageal squamous cell cancer (ESCC) (Guan et al 2020 ). In this study, bioinformatics, ribosome-sequencing (Ribo-seq) dataset, and mass spectrometry (MS) dataset suggested that lncRNA RNF217-AS1 had peptide-coding potential, which was also validated by western blot assay.…”
Section: Introductionmentioning
confidence: 99%